Denervated Myocardium Is Preferentially Associated With Sudden Cardiac Arrest in Ischemic Cardiomyopathy: A Pilot Competing Risks Analysis of Cause-Specific Mortality. (August 2017) - Fallavollita, James A.; Dare, Jonathan D.; Carter, Randolph L.; Baldwa, Sunil; Canty, John M.
Abstract : Background—: Previous studies have identified multiple risk factors that are associated with total cardiac mortality. Nevertheless, identifying specific factors that distinguish patients at risk of arrhythmic death versus heart failure could better target patients likely to benefit from implantable cardiac defibrillators, which have no impact on nonsudden cardiac death. Methods and Results—: We performed a pilot competing risks analysis of the National Institutes of Health–sponsored PAREPET trial (Prediction of Arrhythmic Events with Positron Emission Tomography). Death from cardiac causes was ascertained in subjects with ischemic cardiomyopathy (n=204) eligible for an implantable cardiac defibrillator for the primary prevention of sudden cardiac arrest after baseline clinical evaluation and imaging at enrollment (positron emission tomography and 2-dimensional echo). Mean age was 67±11 years with an ejection fraction of 27±9%, and 90% were men. During 4.1 years of follow-up, there were 33 sudden cardiac arrests (arrhythmic death or implantable cardiac defibrillator discharge for ventricular fibrillation or ventricular tachycardia >240 bpm) and 36 nonsudden cardiac deaths. Sudden cardiac arrest was correlated with a greater volume of denervated myocardium (defect of the positron emission tomography norepinephrine analog 11 C-hydroxyephedrine), lack of angiotensin inhibition therapy, elevated B-type natriuretic peptide, and larger left ventricular end-diastolic volume index. In contrast, nonsudden cardiac death was associated with a higher resting heart rate, older age, elevated creatinine, larger left atrial volume index, and larger left ventricular end-diastolic volume index. Conclusions—: Distinct clinical, laboratory, and imaging variables are associated with cause-specific cardiac mortality in primary-prevention candidates with ischemic cardiomyopathy. If prospectively validated, these multivariable associations may help target specific therapies to those at the greatest risk of sudden and nonsudden cardiac death. Clinical Trial Registration—: URL:https://clinicaltrials.gov . Unique identifier: NCT01400334. Abstract : Supplemental Digital Content is available in the text.